Correlation between Findings in Physical Examination, Magnetic Resonance Imaging, and Nerve Conduction Studies in Lumbosacral Radiculopathy Caused by Lumbar Intervertebral Disc Herniation - Safa Yousif; Afraa Musa; Ammar Ahmed; Ahmed Abdelhai (Advances in Orthopedics)
Purpose. The aim of this study was to find out the correlation between magnetic resonance imaging (MRI) and nerve conduction studies’ (NCS) findings in patients with lumbosacral radiculopathy caused by lumbar intervertebral disc herniation. In addition, the study aimed at finding the correlation between the clinical manifestations of lumbosacral radiculopathy and both MRI and NCS. Patients and Methods. The study was a cross-sectional analytic study which included thirty patients with a history suggestive of lumbosacral radiculopathy. Inclusion criteria were as follows: patients who had an MRI confirmed L4/5 and/or L5/S1 intervertebral disc prolapse in addition to one or more of the following (dermatomal distribution of symptoms appropriate with MRI level, presence of motor weakness, sensory impairment, absent ankle jerk, or positive straight leg raising test). All patients underwent clinical assessment and NCS, and their MRI examination was reviewed. The Chi-Squared/Fisher’s exact test was used to test the correlation. Results. There was a statistically significant correlation between abnormal physical findings and nerve root compression in MRI. Statistically significant correlation was neither found between abnormal physical examination findings and abnormal NCS nor between nerve root compression in MRI and abnormal NCS findings. Conclusion. Abnormal neurological examination findings can be used to predict nerve root compression in MRI examination. On the contrary, positive findings of physical examination do not predict abnormal NCS, as well as negative findings do not exclude abnormal NCS; therefore, it is useful to add NCS when MRI findings do not match clinical examination findings or when no neuroimaging abnormalities can be identified.